Analisis Peranan Akuntansi Dalam Mencegah Dampak Negatif Limbah Terhadap Lingkungan: (Studi Kasus Pada Salah Satu Rumah Sakit Swasta di Denpasar-Bali) - Mudana, I Komang Restu; Indraswarawati, Sang Ayu Putu Arie; Yuniasih, Ni Wayan (Hita Akuntansi dan Keuangan, 2025)
The purpose of this study is to analyze the environmental awareness raised by the findings at Surya Husadha Hospital Ubung-Denpasar. The method of data collection that is used is a qualitative approach that uses methods such as observation, interviews, and literature studies The results of the study indicate that Surya Husadha Hospital has managed hospital waste by cooperating with third parties and making financial records for waste management. Based on the results of the data analysis, it is concluded that although Surya Husadha Hospital has managed to improve its environmental condition, it is still not perfect. The purpose of this study is to enable Surya Husadha Hospital to conduct a more thorough identification, assessment, measurement, presentation, and expression of environmental fees more comprehensively.